Population - Bowen,Ian (London, 1954)
The connection between economic development and population change is not simple, nor necessarily constant over the years. The classical economists bravely under took to define the connection; when their generalizations had been exposed by events as over-simplifications, economists began to drop the discussion altogether, or merely to re-state the older doctrines. Nevertheless, a connection probably exists, and this short study attempts to outline how the student of economics, or the general reader, might now approach the problem. References in the text have been kept as brief as possible. Full references are given at the end in the select bibliography, which may serve as a guide to further reading.
Keywords: Sociology